Genetic Variability Analysis and Association of Traits in Common Bean (Phaseolus vulgaris L.) Landraces Collected from Ethiopia at Jimma - Eyuel Mesera; Garome Shifaraw; Sentayehu Alamerew; Birhanu Amsalu (Advances in Agriculture)
This study was conducted on one hundred common bean landraces at the Jimma Agricultural Research Center, Melko, with the objective of assessing genetic variability and association of traits in common bean landraces collected from different parts of Ethiopia. The experiment was laid out in a simple lattice design with two replications. Analysis of variance showed significant differences among genotypes for all traits. This highly significant difference indicates the existence of large variability among genotypes. High phenotypic coefficients of variation and genotypic coefficients of variation were obtained for plant height (19.43, 11.73), pod length (11.27, 10.69), and 100-seed weight (15.42, 12.74). High heritability in the broad sense was found for days to 50% flowering (66.98), days to 90% maturity (87.43), pod length (90.03), pod width (78.23), harvest index (98.67), and 100-seed weight (68.31). High genetic advance as a percentage of mean with high heritability was obtained for pod length, pod width, harvest index, and hundred seed weight. Grain yield had a positive and significant association with pod length (rp = 0.153∗, rg = 0.282∗∗) and 100-seed weight (rp = 0.294∗∗, rg = 0.492∗∗). Hundred seed weight exerted the highest positive direct effect (0.294) on grain yield at genotypic level. The D2 classified landraces into 7 clusters and one solitary, which makes them moderately divergent. The highest inter-cluster distance was observed between clusters VII and IV. The first five principal components with eigenvalues greater than one altogether explained about 79.56% of the total variation. In conclusion, the top high-yielding landraces, namely, P#1247, P#1092, P#1077, P#861, P#990, P#763, P#58, and P#857, should be included in the next breeding program. 100-seed weight had the highest direct effect and a positive significant association with grain yield. Thus, it should be considered as the selection criteria for further common bean yield improvement. However, the current result is merely indicative and cannot be used to draw definite conclusions. Therefore, the experiment should be replicated in different locations and seasons for greater consistency.